Sustainability and renewable energy: a data envelopment analysis application - Bello, Geovanna Bernardino [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
The current global context presents the challenge of reducing the impact of production and consumption on the environment through the reuse of materials and energy. This dissertation aims to evaluate the performance of countries in this field. The research uses both quantitative and qualitative approaches, with two chapters: the first conducts a bibliometric review on sustainability and Data Envelopment Analysis (DEA), while the second focuses on constructing a renewable energy efficiency indicator through DEA. The results reveal variations in renewable energy efficiency between groups of countries, allowing for benchmarking and identification of nations with low efficiency in the use of renewable energy. The main contribution of this study is the creation of the Renewable Energy Index (REI), which highlights the potential for top 10 global performance in both developed countries (such as Sweden) and developing countries (such as Costa Rica and Sri Lanka). The study reveals that countries in central and northern Europe are among the most efficient, while those with political and economic instability remain among the lowest performers. Furthermore, nations with a predominant agricultural sector, such as Australia and Argentina, exhibited poorer REI performance due to significant methane emissions. This study also contributes to the mitigation of climate change and the advancement of the global sustainability agenda.

O contexto global atual apresenta o desafio de reduzir o impacto da produção e consumo no meio ambiente por meio da reutilização de materiais e energia. Esta dissertação tem como objetivo avaliar o desempenho dos países nesse campo. A pesquisa utiliza abordagens quantitativas e qualitativas, com dois capítulos: o primeiro realiza uma revisão bibliométrica sobre sustentabilidade e análise de envoltória de dados (DEA), enquanto o segundo foca na construção de um indicador de eficiência de energia renovável por meio de DEA. Os resultados revelam variações na eficiência de energia renovável entre grupos de países, permitindo a comparação e identificação de nações com baixa eficiência no uso de energia renovável. A principal contribuição deste estudo é a criação do indicador de energia renovável (REI), que destaca o potencial para as 10 melhores performances globais tanto em países desenvolvidos (como a Suécia) quanto em países em desenvolvimento (como Costa Rica e Sri Lanka). O estudo revela que países da Europa central e do norte estão entre os mais eficientes, enquanto aqueles com instabilidade política e econômica permanecem entre os mais baixos. Além disso, nações com um setor agrícola predominante, como Austrália e Argentina, apresentaram desempenho pior no REI devido a emissões significativas de metano. Este estudo também contribui para a mitigação das mudanças climáticas e o avanço da agenda global de sustentabilidade.
Sustentabilidade e energia renovável: uma aplicação de análise envoltória de dados
Keywords: Data Envelopment Analysis (DEA); Renewable energy efficiency; Indicators; Análise envoltória de dados (DEA); Eficiência de energia renovável; Indicadores